2005
DOI: 10.1038/sj.bjc.6602415
|View full text |Cite
|
Sign up to set email alerts
|

CD1a expression by Barrett's metaplasia of gastric type may help to predict its evolution towards cancer

Abstract: As emerging in the recent literature, CD1a has been regarded as a molecule whose expression may reflect tumour evolution. The aim of the present work was to investigate the expression of CD1a in a series of Barrett's metaplasia (BM), gastric type (GTBM), with and without follow-up, in order to analyse whether its expression may help to diagnose this disease and to address the outcome. Indeed, GTBM may be confused sometimes with islets of ectopic gastric mucosa and its evolution towards dysplasia (Dy) or carcin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 22 publications
2
16
0
Order By: Relevance
“…This is similar to our recent findings regarding metaplasiaadenocarcinoma progression in Barrett's oesophagus, 5,6 which led us to hypothesize a possible co-stimulatory effect of this molecule on the functional immune response. 7 The present data suggest that evaluation of CD1a expression at the LN level by means of molecular diagnostic analyses might help to address the presence of occult micrometastases.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…This is similar to our recent findings regarding metaplasiaadenocarcinoma progression in Barrett's oesophagus, 5,6 which led us to hypothesize a possible co-stimulatory effect of this molecule on the functional immune response. 7 The present data suggest that evaluation of CD1a expression at the LN level by means of molecular diagnostic analyses might help to address the presence of occult micrometastases.…”
Section: Discussionsupporting
confidence: 77%
“…The reaction was carried out using a two-step protocol, with a MyCycler thermal Cycler (BioRad, Milan, Italy). RT-PCR was carried out by mixing 2 g of total RNA, 0.5 lg of pd (T) [12][13][14][15][16][17][18] , 1 lg of pd (N) 6 with RNase-free water. The reaction comprised a reverse transcription step of 30 min (42°C), followed by inactivation of the enzyme at 95°C (5 min).…”
Section: Reverse Transcriptase-pcrmentioning
confidence: 99%
See 1 more Smart Citation
“…[18][19][20] CD1a has also been tested as a possible biomarker of Barrett's metaplasia, in the hope that its expression might help in predicting the prognosis of this pathology. 21 The markers p53 and c-erbB2 in particular have been controversially discussed. TP53 was found to have a low sensitivity, but p53 mutational status may ultimately be a component of such a molecular marker panel.…”
Section: Ink4amentioning
confidence: 99%
“…[9][10][11] A variety of inflammatory and immune cells populate the Barrett's esophagus mucosa, including T and B lymphocytes, mast cells, and macrophages. [12][13][14] We recently reported that antigen-presenting dendritic cells are present in Barrett's esophagus with a significant increase in their spatial density in adenocarcinoma compared to benign Barrett's esophagus. 14 Dendritic cells are powerful initiators and regulators of immune reactions [15][16][17][18][19] and thus may have a role in the pathogenesis of Barrett's esophagus and adenocarcinoma.…”
Section: Introductionmentioning
confidence: 99%